2012
DOI: 10.1088/1674-1056/21/7/076101
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication processing effects on the microstructure and morphology of erbium film

Abstract: Fabrication processing effects on the microstructure and morphology of erbium film * Shen Hua-Hai(申华海) a) , Peng Shu-Ming(彭述明) b) , Long Xing-Gui(龙兴贵) b) , Zhou Xiao-Song(周晓松) b) , Yang Li(杨 莉) a) , Liu Jin-Hua(刘锦华) b) , Sun Qing-Qiang(孙庆强) a) , and Zu Xiao-Tao(祖小涛) a) †

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…To get more fitting data of the Mo-Er system, we calculate the surface energies of (1 0 0), (1 1 1) and (1 1 0) surfaces of bcc Mo using the VASP code, and find the (1 1 0) surface is energetically more favorable than the other two surfaces. Moreover, the (1 1 0), (2 0 0) and (2 2 1) planes of Mo were evidently observed in the experimental results of as-growth erbium films [9,30]. Therefore, the (1 1 0) surface of bcc Mo is possibly favorable for Er growth, and the adsorption behavior of Er on the Mo (1 1 0) surface is mainly studied in the present work.…”
Section: Fitting Methodologymentioning
confidence: 77%
See 2 more Smart Citations
“…To get more fitting data of the Mo-Er system, we calculate the surface energies of (1 0 0), (1 1 1) and (1 1 0) surfaces of bcc Mo using the VASP code, and find the (1 1 0) surface is energetically more favorable than the other two surfaces. Moreover, the (1 1 0), (2 0 0) and (2 2 1) planes of Mo were evidently observed in the experimental results of as-growth erbium films [9,30]. Therefore, the (1 1 0) surface of bcc Mo is possibly favorable for Er growth, and the adsorption behavior of Er on the Mo (1 1 0) surface is mainly studied in the present work.…”
Section: Fitting Methodologymentioning
confidence: 77%
“…One of the most challenging is lack of safe, reliable, compact and effective hydrogen storage technologies [1,2]. Rare-earth metal erbium (Er) has been extensively studied in theory and experiments in recent years [3][4][5][6][7][8][9][10][11][12]. The majority factor for the potential application of erbium is that erbium hydrides readily absorb hydrogen and have high thermal stability in comparison to titanium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,[15][16][17][18] The structure of films could involve a number of characteristics, such as grain size, strain, crystallographic orientation, and so on. It was shown that the film structure was strongly affected by the preparation procedures and deposition condition, such as substrate temperature, [19,20] deposition rate, [21] substrate materials, [22] impurity contamination, and film thickness. [23][24][25] The purpose of this paper is to study 3 He migration in TiT 1.9 films.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] The single electron transistor (SET) is one of the most investigated nanodevices in recent years. [9][10][11][12][13] The photolithography, electron-beam lithography (EBL), electronbeam evaporation, and lift-off procedures are commonly used techniques in SET production. As mentioned before, the dual beam system is a nano-lithography alternative, and some efforts have been made to investigate the SET using FIBID or FEBID techniques.…”
Section: Introductionmentioning
confidence: 99%